A History of the Concept of Interpersonal Relations in Nursing Based on the Psychiatric Nursing Textbook Literature. (2nd January 2023) - Clark, Greg
Abstract: Many nurses would assume that interpersonal relations in nursing is a reasonably modern concept that originated with work of Hildagarde Peplau in 1952. However, there is evidence of concepts and ideas that resonate with interpersonal relations being evident in the psychiatric nursing textbook literature from its beginnings in 1885. The aim of this article is to provide an outline of ideas about interpersonal relations in nursing as presented in the psychiatric nursing textbook literature between 1885 and 2013 and trace the development of these ideas over that timeframe.This study uses Bevir's methodology known as The Logic of the History of Ideas. This is a post-analytical framework. Concepts related to interpersonal relation in nursing can be found throughout the psychiatric nursing textbook literature. The language may not be consistent with current language use but nevertheless, the ideas and concepts evident in the literature do demonstrate a consistent presence of thinking about interpersonal relations.